Synthesis of CdS and alloyed CdMnS nanocrystals using aqueous foams - Kumar, P. Senthil; Kasture, Manasi; Raghavan, U; Pasricha, R; Sastry, M (Journal of Nanoscience and Nanotechnology, 2005)
Certain surfactant-stabilized aqueous foams provide a potentially efficient and simple chemical route for the synthesis of various nanomaterials with controllable structure, size, and shape. In the present work, a one-step process for the synthesis of CdS and Cdl(1-x)Mn(x)S (0 < x < 10) nanocrystals has been described. Aqueous CdCl2 and the aerosol-OT solutions are homogeneously mixed together and thereafter, nitrogen is bubbled through this solution to produce stable aqueous foam. After drainage of the foam, the freestanding dry foam consisting of cadmium cations electrostatically complexed with the anionic aerosol-OT molecules at the liquid-gas interface is treated with H2S vapor. The foam turns yellowish-orange and collapses, in the process yielding CdS nanoclusters of variable morphology. This morphology variation is appropriately attributed to growth of the CdS as well as alloyed Cd1-xMnxS nanoparticles in different regions of the foam contributing to the varying topological structure. Optical absorption spectra of both CdS and Cd1-xMnxS nanoparticles clearly show a well-defined exciton absorption feature around 450 nm due to quantum confinement effects. The interesting band edge emission characteristics of these AOT-capped CdS and Cd1-xMnxS nanoparticles produced in the foam are discussed with respect to their size and shape. Particular interest in the present novel aqueous foam approach arises due to the fact that the cubic zincblende CdS and alloyed Cd1-xMnxS nanocrystals could easily be obtained even under ambient experimental conditions itself.
Keywords: absorption and fluorescence; aerosol-OT; alloyed CdMnS nanocrystals; aqueous foams; CdS nanoclusters; quantum confinement; zincblende

Controllable synthesis of SnO2 photocatalyst with superior photocatalytic activity for the degradation of methylene blue dye solution - Prakash, K.; Kumar, P. Senthil; Pandiaraj, S.; Saravanakumar, K.; Karuthapandian, S. (Journal of Experimental Nanoscience, 2016)
SnO2 photocatalyst was successfully synthesised by novel chemical route in hydrothermal environment and annealed at two different temperatures viz 550 and 600 degrees C, respectively. The crystal structure, optical properties, surface and bulk morphology have been characterised using various tools like X-ray diffraction (XRD), UV visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscope (TEM) and scanning electron microscope (SEM). Cubic, spheres and porous like morphology of SnO2 photocatalyst was successfully confirmed using SEM micrographs and TEM. In addition to this the photocatalytic activity was evaluated towards the degradation of methylene blue dye solution. SnO2 photocatalyst annealed at 600 degrees C exhibits excellent photocatalytic efficiency which may be attributed to the unique morphology, high crystalline nature and charge separation. The photocatalyst efficiency was further tested towards the concentration of dye, catalyst dosage and pH of the dye. The involvement of center dot OH in the photocatalytic reaction was evidenced using trapping experiment by employing different scavengers. The photocatalyst was moderately active, stable upto its fifth usage and stability of the photocatalyst before and after the photocatalytic reaction was also been studied using XRD and SEM.